(untitled) (Journal of Medicine, 2013)
Background: Epidemiologic studies have identified hyper-homocysteinemia as a possible risk factor for atherosclerosis.The aim of my study was based on evaluation of relationship between homocysteinemia with ischemic stroke patients. Methods and materials: It was a prospective observational study conducted in the Department of Neurology, Sir Salimullah Medical College & Mitford hospital, Dhaka. Thirty six consecutive patients with ischemic stroke were analyzed by serum total homocysteine, total cholesterol, HDL-cholesterol, LDL-cholesterol, triglyceride and Equal number of controls same ages were compared with the case group. Result: Mean Fasting blood sugar, serum fasting total cholesterol (TC), serum fasting Low density lipoprotein (LDL) were significantly higher in case group (p=0.001). Serum TC and LDL had a positive correlation with serum homocystine a (p=0.001). Serum High density lipoprotein (HDL) had a negative correlation (p=0.718) and serum triglyceride (TG) had a negative correlation (p = 0.182). Total plasma fasting homocysteine level in case group was 21.89 ± 9.38 ìmol/l and control group was 12.31 ± 3.27 ìmol/l, (p=0.001). Elevated fasting homocystein level was found in 75.0% of ischemic stroke patient and in 16.67% of healthy controls (p=0.001). The incidence of hyperhomocysteinemia is higher in ischaemic stroke cases than that in age-sex matched healthy controls. Conclusion: Hyperhomocysteinemia in ischaemic stroke patients has as been determined as vascular risk factor in our study. Significant correlation has been found between homocysteine concentration and ischaemic stroke. DOI: http://dx.doi.org/10.3329/jom.v14i1.14536 J MEDICINE 2013; 14 : 47-51